Wafer‐Scale Fabrication of Nanopore Devices for Single‐Molecule DNA Biosensing using MoS2. Issue 11 (11th May 2020) - Thakur, Mukeshchand; Macha, Michal; Chernev, Andrey; Graf, Michael; Lihter, Martina; Deen, Jochem; Tripathi, Mukesh; Kis, Andras; Radenovic, Aleksandra
Abstract: Atomically thin (2D) nanoporous membranes are an excellent platform for a broad scope of academic research. Their thickness and intrinsic ion selectivity (demonstrated for example in molybdenum disulfide‐MoS2 ) make them particularly attractive for single‐molecule biosensing experiments and osmotic energy harvesting membranes. Currently, one of the major challenges associated with the research progress and industrial development of 2D nanopore membrane devices is small‐scale thin‐film growth and small‐area transfer methods. To address these issues, a large‐area protocol including a wafer‐scale monolayer MoS2 synthesis, Si/SiN x substrate fabrication and wafer‐scale material transfer are demonstrated. First, the 7.62 cm wafer‐scale MOCVD growth yielding homogenous monolayer MoS2 films are introduced. Second, a large number of devices are fabricated in one batch by employing the wafer‐scale thin‐film transfer method with high transfer efficiency (>70% device yield). The growth, the transfer quality and cleanliness are investigated using transmission electron microscopy, atomic force microscopy and Raman spectroscopy. Finally, the applicability and robustness of the large‐area protocol is demonstrated by performing a set of double‐stranded DNA translocation experiments through as‐fabricated MoS2 nanopore devices. It is believed that the shown approach will pave the way toward wafer‐scale, high‐throughput use of 2D nanopores in various applications. Abstract : Combination of a large‐area (7.62 cm) synthesis of a homogenous molybdenum disulfide (MoS2 ) monolayer films with a hybrid large‐scale transfer method is used to establish a batch fabrication protocol of nanopore devices. Applicability, efficiency, and fabrication yield are demonstrated for single‐molecule DNA biosensing applications. The challenges and opportunities for presented large‐scale methods are discussed.